Tumor-associated neutrophils as a new prognostic factor in cancer: a systematic review and meta-analysis. - Meixiao Shen; Pingping Hu; Frede Donskov; Guanghui Wang; Qi Liu; Jiajun Du (PLoS ONE, 2014)
Purpose Tumor-associated neutrophils (TAN) have been reported in a variety of malignancies. We conducted an up-to-date meta-analysis to evaluate the prognostic role of TAN in cancer. Method Pubmed, Embase and web of science databases were searched for studies published up to April 2013. Pooled hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs) were calculated. The impact of neutrophils localization and primary antibody were also assessed. Results A total of 3946 patients with various solid tumors from 20 studies were included. High density of intratumoral neutrophils were independently associated with unfavorable survival; the pooled HRs were 1.68 (95%CI: 1.36-2.07, I2 = 55.8%, p<0.001) for recurrence-free survival (RFS)/disease-free survival (DFS), 3.36 (95%CI: 2.08-5.42, I2 = 0%, p<0.001) for cancer-specific survival (CSS) and 1.66 (95%CI: 1.37-2.01, I2 = 70.5%, p<0.001) for overall survival (OS). Peritumoral and stromal neutrophils were not statistically significantly associated with survival. When grouped by primary antibody, the pooled HRs were 1.80 (95%CI: 1.47-2.22, I2 = 67.7%, p<0.001) for CD66b, and 1.44 (95%CI: 0.90-2.30, I2 = 45.9%, p = 0.125) for CD15, suggesting that CD66b positive TAN might have a better prognostic value than CD15. Conclusion High levels of intratumoral neutrophils are associated with unfavorable recurrence-free, cancer-specific and overall survival.